Context-Aware Trust Prediction for Optimal Routing in Opportunistic IoT Systems - Abdulkadir Abdulahi Hasan; Xianwen Fang; Sohaib Latif; Adeel Iqbal (Sensors, 2025)
The Social Opportunistic Internet of Things (SO-IoT) is a rapidly emerging paradigm that enables mobile, ad-hoc device communication based on both physical and social interactions. In such networks, routing decisions heavily depend on the selection of intermediate nodes to ensure secure and efficient data dissemination. Traditional approaches relying solely on reliability or social interest fail to capture the multifaceted trustworthiness of nodes in dynamic SO-IoT environments. This paper proposes a trust-based route optimization framework that integrates social interest and behavioral reliability using Bayesian inference and Jeffrey’s conditioning. A composite trust level is computed for each intermediate node to determine its suitability for data forwarding. To validate the framework, we conduct a two-phase simulation-based analysis: a scenario-driven evaluation that demonstrates the model’s behavior in controlled settings, and a large-scale NS-3-based simulation comparing our method with benchmark routing schemes, including random, greedy, and AI-based protocols. Results confirm that our proposed model achieves up to an <semantics>88.9%</semantics> delivery ratio with minimal energy consumption and the highest trust accuracy (<semantics>86.5%</semantics>), demonstrating its robustness and scalability in real-world-inspired IoT environments.